Air pollution monitoring system in semi enclosed building for agricultural sector - S., Nurulain; Najib, Muhammad Sharfi; E., Lewis; Salim, M. R.; Manap, H. (IOP Publishing, 2020)
This paper describes the development of an optical sensor system to monitor ammonia emission in the agricultural sector. At initial stage, an open path optical technique where a cylindrical chamber is used to detect low ammonia concentration within the Ultraviolet region. The methodology describing the operation of the sensor with wavelengths combination technique to optimize the measurement is presented. The results show the sensor is best measuring ammonia concentration at combination wavelengths (around 212 nm) with the Lower Detection Limit of 2.25 ppm and 1 s response time is achieved. Then the system is tested to monitor ammonia pollution in the cattle barn in Tipperary, Ireland. It shows that the developed system is able to detect and measure very low ammonia concentration which is less than 2 ppm.